Hyperglycaemic memory affects the neurovascular unit of the retina in a diabetic mouse model - Friedrichs, Patrick; Schlotterer, Andrea; Sticht, Carsten; Kolibabka, Matthias; Hammes, Hans-Peter (Diabetologia, 2017)
Aims/hypothesis: The aim of this study was to evaluate damage to the neurovascular unit in a mouse model of hyperglycaemic memory. Methods: A streptozotocin-induced mouse model of diabetes (C57BL/6J background) received insulin-releasing pellets and pancreatic islet-cell transplantation. Damage to the neurovascular unit was studied by quantitative retinal morphometry for microvascular changes and microarray analysis, with subsequent functional annotation clustering, for changes of the retinal genome. Results: Sustained microvascular damage was confirmed by persistent loss of pericytes in the retinal vasculature (PC/mm2): compared with healthy controls (1981 ± 404 PC/mm2), the pericyte coverage of the retinal vasculature was significantly reduced in diabetic mice (1571 ± 383 PC/mm2, p < 0.001) and transplanted mice (1606 ± 268 PC/mm2, p < 0.001). Genes meeting the criteria for hyperglycaemic memory were attributed to the cytoskeletal and nuclear cell compartments of the neurovascular unit. The most prominent regulated genes in the cytoskeletal compartment were Ddx51, Fgd4, Pdlim7, Utp23, Cep57, Csrp3, Eml5, Fhl3, Map1a, Mapk1ip1, Mnda, Neil2, Parp2, Myl12b, Dynll1, Stag3 and Sntg2, and in the nuclear compartment were Ddx51, Utp23, Mnda, Kmt2e, Nr6a1, Parp2, Cdk8, Srsf1 and Zfp326. Conclusions/interpretation: We demonstrated that changes in gene expression and microvascular damage persist after euglycaemic re-entry, indicating memory.